Correlation of osteoprotegerin, sRANKL, inflammatory factors and epicardial adipose tissue volume with coronary heart disease. Issue 7 (27th April 2021) - He, Qiong; Ming, Dan; Chen, Dan; Zhang, Chuanlin; Xie, Hui; Wei, Shuang
Abstract: Background: To observe the correlation of osteoprotegerin, soluble receptor activator of nuclear factor‐κB ligand (sRANKL), inflammatory factors and epicardial adipose tissue volume (EATV) with the severity of coronary heart disease (CHD). Methods: We studied 390 patients who were admitted to the Department of Cardiology of our hospital because of chest pain and underwent coronary angiography (CAG) from August 2018 to December 2019. According to CAG, 209 patients had non‐CHD and 181 patients had CHD. Demographic data, biochemical indicators including low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C), total cholesterol (TC), lipoprotein a (Lp(a)), apolipoprotein B (apoB), apolipoprotein AI (apoAI), creatine kinase isoenzyme (CK‐MB), osteoprotegerin, sRANKL, inflammatory factors (hs‐CRP, FIB and IL‐6), and EATV were collected. Results: The number of males, age, diabetes and hypertension in the CHD group was higher than those in the non‐CHD group ( P < .05). LDL‐C, TC and apoB in the two groups were not significantly different ( P > .05); HDL‐C and apoAI in the CHD group were lower than those in the non‐CHD group, and Lp(a) and CK‐MB were higher than those in the control group ( P < .05). Osteoprotegerin, IL‐6, hs‐CRP, EATV and FIB in the CHD group were higher than those in the non‐CHD group, while sRANKL was lower than that in the control group ( P < .05). Pearson correlation analysis showed that osteoprotegerin, sRANKL, inflammatory factors (hs‐CRP, FIB and IL‐6) and EATV were correlated with the severity of CHD ( P < .05). Multivariate logistic regression analysis showed that CK‐MB, osteoprotegerin, sRANKL, inflammatory factors (hs‐CRP, FIB and IL‐6) and EATV were risk factors for CHD, while HDL‐C, Lp(a), apoAI were protective factors. Conclusion: Osteoprotegerin, sRANKL, inflammatory factors and EATV were positively correlated with the severity of CHD, which had certain value for the diagnosis of CHD.